Precision Compensation Control of a Piezo-Scanning Mechanism - Liu, Shuxin; Jiang, Huhai; Huang, Xiaohong; She, Junchao; Si, Chen; Lv, Shengqiang (Frontiers in Materials, 2022)
In this study, a controller based on two compensators is developed to support a two-axis piezo-scanning mechanism for tracking control. The hysteresis compensator is designed based on a Prandtl–Ishlinskii hysteresis model in order to reduce the nonlinear hysteresis effect of a piezoelectric actuator. Furthermore, to compensate for uncertainties due to parametric variations, hysteresis-compensated error, and un-modeled dynamics, the uncertainties compensator based on the neural network disturbance observer is proposed. The developed controller is verified with regard to control performance by experiment. Those two observers are used to complete hysteresis compensation and disturbance compensation, which will not reduce the stability and bandwidth of the system and improve the control accuracy. Experimental results show that the proposed hybrid controller can overcome the mentioned nonlinearity and uncertainty efficiently and preserve good positioning accuracy with high-bandwidth varying frequencies (1–150 Hz).